Analysis of The Effect of Motivation and Job Satisfaction on Employee Performance in PT Gagas Energi Indonesia Jakarta - Suardhita , Nyoman; Rafik, Ahmad; Siregar, Otto (AGUSPATI Research Institute, 2020)
Human resources are one of the main elements that occupy a very strategic position, meaning that the human element plays a very important role in carrying out activities to achieve company goals. For this reason, high motivation and job satisfaction are needed to improve employee performance which in turn will increase the competitiveness of the company. The purpose of this study is to determine and analyze motivation and job satisfaction both partially and simultaneously on employee performance. This research was conducted at PT. Gagas Energi Indonesia towards 100 employees and the data collected is processed with multiple regressions with SPSS version 25. The results show that motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, motivation, and job satisfaction simultaneously have a positive effect and significant to Employee Performance.